A Prolonged Dilemma: Traditional Curriculum of Arabic Rhetoric (Balaghah) in Malaysia - Abdul Hakim, Abdullah; Mustafa, Che Omar (2016)
One of the important components of Arabic language is rhetoric (balaghah). The purpose of Arabic rhetoricis to develop Arabic competence and foster literary appreciation. By mastering Arabic rhetoric, learners can produce correct, beautifully worded and appropriate sentences. The teaching of Arabic rhetoric officially started through the Islamic Education curriculum in Malaysia with the introduction of the madrasah system in the early 20th century. However, there are some obstacles and criticisms in its teaching in Malaysia. This study analysed five studies on the teaching of Arabic rhetoric conducted by local scholars supported by sixteen studies on the same issue conducted by Arab scholars. These works were selected because they represent authentic studies conducted by prominent practitioners and scholars of the subject. This study concludes that problems encountered in teaching Arabic rhetoric the selection of objectives, contents, examples, teaching methodology as well as assessment. Therefore, in order to ensure the efficient implementation of its teaching, the Arabic rhetoric should be re-assessed. This study also provides suggestions to ensure the implementation of teaching Arabic rhetoric in line with the language teaching theory and that the purpose and objectives are achieved.